2013
DOI: 10.1002/2013gl057582
|View full text |Cite
|
Sign up to set email alerts
|

An open ocean region in Neoproterozoic glaciations would have to be narrow to allow equatorial ice sheets

Abstract: [1] A major goal of understanding Neoproterozoic glaciations and determining their effect on the evolution of life and Earth's atmosphere is establishing whether and how much open ocean there was during them. Geological evidence tells us that continental ice sheets had to flow into the ocean near the equator during these glaciations. Here we drive the Parallel Ice Sheet Model with output from four simulations of the ECHAM5/Max Planck Institute Ocean Model atmosphere-ocean general circulation model with success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…In an extension of that work, Hoffman et al () found the deglaciated areas in Benn et al () were able to occasionally reach above‐freezing temperatures. In contrast, using different models, Donnadieu et al () and Rodehacke et al () were unable to produce deglaciated land in other Snowball Earth experiments, suggesting that the details of the ice sheet model matter and are one of the key caveats of our results. Our goal was to use a simple approach to identify the impact that ice sheet elevation could have on our results and find that very large ice sheets are a problem, but thinner ice sheets may not be.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In an extension of that work, Hoffman et al () found the deglaciated areas in Benn et al () were able to occasionally reach above‐freezing temperatures. In contrast, using different models, Donnadieu et al () and Rodehacke et al () were unable to produce deglaciated land in other Snowball Earth experiments, suggesting that the details of the ice sheet model matter and are one of the key caveats of our results. Our goal was to use a simple approach to identify the impact that ice sheet elevation could have on our results and find that very large ice sheets are a problem, but thinner ice sheets may not be.…”
Section: Discussioncontrasting
confidence: 74%
“…PlaSim has been used before to study snowball events on Earth‐like planets (e.g., Boschi et al, ; Linsenmeier et al, ; Lucarini et al, ) and is able to reproduce snowball phenomena found using other models by Pierrehumbert (), Abbot, Voigt, et al (), and Abbot (), such as increased variability in troposphere lapse rate, reduced tropopause height, weakened extratropical winter lapse rates, and warming of snowball states by cloud forcing. Models disagree on the extent of sea ice coverage during snowball events (e.g., Kirschvink, ; Lewis et al, ; Rodehacke et al, ; Yang et al, ), but in PlaSim, snowballs are characterized by complete sea ice cover, and exit from a snowball event begins when sea ice starts to melt, triggering an albedo feedback runaway. Sea ice thickness is limited to 9 m, but we do not restrict the depth of land ice and snow.…”
Section: General Circulation and Weathering Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The only place where a sea glacier cannot penetrate a channel is in a region of net sublimation, which, according to GCM results for Snowball Earth are mostly near the equator [ Pierrehumbert et al ., ; Pollard and Kasting , , Figure 9]. Since inland seas are allowed only in regions of net sublimation, any land areas surrounding the inland sea would likely be desert, covered with bare rock or soil, not snow or ice, although others have indicated that some or all of the land in regions of net sublimation could become covered with land ice flowing from regions of net accumulation [ Donnadieu et al ., ; Pollard and Kasting , ; Rodehacke et al ., ]. If it is unglaciated, the low albedo of the rock and soil surrounding the inland sea would increase absorbed radiation and locally increase the air temperature.…”
Section: Discussionmentioning
confidence: 99%
“…5 ), whereas Marinoan ones accumulated during the drift stage of post-rift subsidence. If true, active rift flanks may have increased Sturtian paleotopography, resulting in more complete coverage of the continents by ice sheets ( 165 , 166 ), most importantly by glacial flow into the equatorial zone of sublimation. This would have raised the planetary albedo.…”
Section: Cryogenian Chronology and Paleogeographymentioning
confidence: 99%